Nimbolide Inhibits SOD2 to Control Pancreatic Ductal Adenocarcinoma Growth and Metastasis - Tugba Mehmetoglu-Gurbuz; Rajkumar Lakshmanaswamy; Karla Perez; Mayra Sandoval; Casandra A. Jimenez; Jackelyn Rocha; Rachel Madeline Goldfarb; Courtney Perry; Alejandra Bencomo; Nishkala Neela; Jose A. Barragan; Raquel Sanchez; et al. (MDPI AG, 2023)
Reactive oxygen species are frequently associated with various cancers including pancreatic ductal adenocarcinomas (PDACs). Superoxide dismutase 2 (SOD2) is an enzyme that plays an important role in reactive oxygen species (ROS) signaling. Investigating the molecular function and biological functions of SOD2 can help us develop new therapeutic options and uncover new biomarkers for PDAC diagnosis and prognosis. Here, we show that nimbolide (NB), a triterpene limonoid, effectively blocks the growth and metastasis of PDACs by suppressing the expression and activity of SOD2. To identify the role of SOD2 in NB-induced anticancer activity, we used RNA interference to silence and plasmid transfection to overexpress it. Silencing SOD2 significantly reduced the growth and metastatic characteristics like epithelial-to-mesenchymal transition, invasion, migration, and colony-forming capabilities of PDACs, and NB treatment further reduced these characteristics. Conversely, the overexpression of SOD2 enhanced these metastatic characteristics. ROS signaling has a strong feedback mechanism with the PI3K/Akt signaling pathway, which could be mediated through SOD2. Finally, NB treatment to SOD2-overexpressing PDAC xenografts resulted in significant inhibition of tumor growth and metastasis. Overall, this work suggests that NB, a natural and safe phytochemical that silences SOD2 to induce high levels of ROS generation, results in increased apoptosis and reduced growth and progression of PDACs. The role of SOD2 in regulating NB-induced ROS generation presents itself as a therapeutic option for PDACs.